The Effect of the Financial Crisis on the Taxation of Consumption, Labour, and Capital in the European Union; Wpływ kryzysu na opodatkowanie konsumpcji, pracy i kapitału w Unii Europejskiej - Anna Krajewska (Comparative Economic Research. Central and Eastern Europe, 2013)
The impact of the current financial crisis on changes in the taxation of consumption, labour, and capital in the European Union. The responses reflected in the tax policies pursued in the EU countries to the current crisis will be analysed in three ways: 1. Distribution of total tax burden by economic function, i.e. assessment of the share of taxes on consumption, labour, and capital in relation to GDP and total tax revenues. Therefore, the analysis will cover backward-looking ta Xburden indicators; 2. Analysis of trends in the implicit tax rate (ITR) on consumption, labour and capital. The ITR is an indicator which expresses the relation of tax burdens levied on different activities to total revenue from this activity. The ITR takes into account the legislation and the resulting tax burden(s) which may affect the behaviour of various entities and their decisions. This approach is described as forward-looking effective tax rate; 3. Trends in the EU countries are compared with the changes taking place in Poland. This includes an explanation of the specificity of the fiscal policy pursued in Poland. 4. For the purpose of this paper we used statistics prepared according to the methodology adopted by the European Commission, published in "Taxation trends in the European Union", Eurostat 2012. – – Celem artykułu jest pokazanie wpływu kryzysu na zmiany w opodatkowaniu konsumpcji, pracy i kapitału w roźṅych krajach UE. Reakcja polityki podatkowej na obecny kryzys bedzie analizowana w trzech aspektach: 1. Analiza obciazėnṕodatkowych rozpatrywanych według ich ekonomicznych funkcji, czyli udział podatkoẃ obciazȧjacych konsumpcje, prace i kapitał w łacznych dochodach budzėtowych z podatkoẃ oraz w relacji do PKB. 2. Analiza trendoẃ dotyczacych ukrytych (efektywnych) stawek opodatkowania (the implicite tax rate - ITR) konsumpcji, pracy i kapitału. ITR jest wskazńikiem, ktoŕy pokazuje relacje miedzy obciazėniami podatkowymi nakładanymi na dany rodzaj aktywnosći gospodarczej (konsumpcje, prace lub kapitał) i łacznymi dochodami osiaganymi z okresĺonego rodzaju aktywnosći. ITR uwzglednia legislacyjne aspekty podatkoẃ i inne czynniki wpływajace na ostateczne obciazėnia podatkowe, a zatem wywiera wpływ na zachowania roźṅych podmiotoẃ gospodarczych i podejmowanych przez nich decyzji. 3. Trendy obserwowane w krajach UE sa poroẃnywane ze zmianami dokonujacymi sie w Polsce. Skłania to zarazem do przedstawienia specyfiki polityki fiskalnej prowadzonej w Polsce w ostatnich latach. Materiały statystyczne wykorzystane w artykule pochodza z opublikowanego przez Komisje Europejska raportu: "Taxation trends in the European Union", Eurostat 2012.
Keywords: 330